Interviewing asylum seekers: A vignette study on the questions asked to assess credibility of claims about origin and persecution. Issue 1 (2nd November 2016) - van Veldhuizen, Tanja S.; Horselenberg, Robert; Landström, Sara; Granhag, Pär Anders; van Koppen, Peter J.
Abstract: The aim of the current vignette study is to map the style, type, and themes of questions that are asked when assessing the credibility of asylum seekers' claims. Sixty‐five officials from the Swedish Migration Agency ( Migrationsverket ), were asked to respond to one out of four different vignettes that contained fictitious asylum narratives. Each vignette presented the types of problems often encountered by officials at the migration board. Two of the vignettes contained no evidence of the origin of the asylum seeker. The other two contained no evidence for the claim of persecution. The asylum officials were asked to formulate five questions that would help them to assess the veracity of the applicant's claim. Our analyses showed that they mainly formulated open questions in an information gathering style. A thematic analysis of the questions revealed that when a claim about origin was assessed, asylum officials mostly asked questions about life in the country of origin, identity documents, and the flight to Europe. When the claim about persecution was assessed, in contrast, asylum officials mostly formulated case‐specific questions (e.g., how the applicant was arrested). Hence, when the credibility of claims about origin is assessed, there seems to be a typical set of questions that asylum officials use. The asylum officials seem to assume that if the applicant is truly originating from a specific country or area, he or she should have ample knowledge about that area, its customs, and frequently encountered objects.